Incorporation of resident macrophages in engineered tissues: multiple cell type response to microenvironment controlled macrophage-laden gelatin hydrogels - Dollinger, Camille; Ciftci, Sait; Knopf-Marques, Helena; Ghaemmaghami, Amir M.; Debry, Christian; Barthes, Julien; Vrana, Nihal Engin (Wiley, 2018)
The success of tissue engineering strategy is strongly related to the inflammatory response, mainly through the activity of macrophages that are key cells in initial immune response to implants. For engineered tissues, the presence of resident macrophages can be beneficial for maintenance of homeostasis and healing. Thus, incorporation of macrophages in engineered tissues can facilitate the integration upon implantation. In this study, we developed an in-vitro model of interaction between encapsulated naive monocytes, macrophages induced with M1/M2 stimulation and incoming cells for immune assisted tissue engineering applications. To mimic the wound healing cascade, Naive THP-1 monocytes, endothelial cells, and fibroblasts were seeded on the gels as incoming cells. The interaction was first monitored in the absence of the gels. In order to mimic resident macrophages, THP-1 cells were encapsulated in the presence or absence of IL-4 to control their phenotype and then these hydrogels were seeded with incoming cells. Without encapsulation, activated macrophages induce apoptosis in endothelial cells. Once encapsulated no adverse effects were seen. Macrophage-laden hydrogels attracted more endothelial cells and fibroblasts compared to monocytes-laden hydrogels. The induction (M2 stimulation) of encapsulated macrophages did not change the overall number of attracted cells; but significantly affected their morphology. M1 stimulation by a defined media resulted in secretion of both pro and anti-inflammatory cytokines compared to M2 stimulation. We demonstrated that there is a distinct effect of encapsulated macrophages on the behavior of the incoming cells; this effect can be harnessed to establish a microenvironment more prone to regeneration upon implantation.